2016
DOI: 10.1186/s40687-016-0082-9
|View full text |Cite
|
Sign up to set email alerts
|

The Lerch zeta function IV. Hecke operators

Abstract: This paper studies algebraic and analytic structures associated with the Lerch zeta function. It defines a family of two-variable Hecke operators {T m : m ≥ 1} given byacting on certain spaces of real-analytic functions, including Lerch zeta functions for various parameter values. The actions of various related operators on these function spaces are determined. It is shown that, for each s ∈ C, there is a two-dimensional vector space spanned by linear combinations of Lerch zeta functions characterized as a max… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…It also bears the name of Lerch [19], who showed that for ℑz > 0 and q ∈ (0, 1) the functional equation ζ(z, q; 1 − s) = (2π) −s Γ(s) e( 1 4 s − zq)ζ(−q, z; s) + e(− 1 4 s + zq)ζ(q, 1 − z; s) holds; this is called Lerch's transformation formula. For an interesting account of the analytic properties of the Lipschitz-Lerch zeta function and related functions, we refer the reader to the work of Lagarius and Li [15][16][17][18]; see also Apostol [2].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…It also bears the name of Lerch [19], who showed that for ℑz > 0 and q ∈ (0, 1) the functional equation ζ(z, q; 1 − s) = (2π) −s Γ(s) e( 1 4 s − zq)ζ(−q, z; s) + e(− 1 4 s + zq)ζ(q, 1 − z; s) holds; this is called Lerch's transformation formula. For an interesting account of the analytic properties of the Lipschitz-Lerch zeta function and related functions, we refer the reader to the work of Lagarius and Li [15][16][17][18]; see also Apostol [2].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…Φ(s, z, c)) is a simultaneous eigenfunction, acting on various function spaces. Part IV ( [47]) of this series considers such operators on a function space with real variables. These additional discrete symmetries together with the differential equation (1.12) suggest that there should be an automorphic interpretation of the Lerch zeta function, made in terms of the related functions L ± (s, a, c).…”
Section: Further Directionsmentioning
confidence: 99%
“…e.g. [35]. In the last few decades, the most fundamental and influential works related to the Lerch zeta-function are [16], [43], [47], and [71], which are partly incorporated in [10].…”
Section: Introductionmentioning
confidence: 99%